PERANAN CU MANDIRI BAGI PENINGKATAN KESEJAHTERAAN ANGGOTA DI KABUPATEN SERDANG BEDAGAI - Badrun Badrun; Paidi Hidayat (Ekonomi dan Keuangan, 2013)
Abstract : Cooperation is an organization that launched and supported by the government for the purpose of public welfare. The existence of cooperation in Serdang Bedagai Regency aims to build the economy of the people that are expected to improve the economic welfare of the community by increasing revenue.The purpose of this study is to analyze how much the development of CU Mandiri in Serdang Bedagai Regency, analyze how much influence the characteristics of the members to the success of CU Mandiri in Serdang Bedagai Regency, analyze how much influence the CU Mandiri on income members in Serdang Bedagai Regency, as well as to determine the amount of savings and influential members of the loan amount to the success of the Credit Union. The method used in this research is to use the Rank Spearman correlation test and multiple linear regression analysis.The result showed that the CU Mandiri shows the development of the number of members, number of deposits, loan amount, and the asset is increasing every year. Based on the Rank Spearman correlation test was explained that the variable characteristics of members (age, education, number of dependents, and income) are not closely related to the dividend variable statistically. Based on the results of the t-test showed savings and loan variable positive and significant impact on the income variable statistically. Based on the results of t-test variables have positive and significant savings to variable dividends while the loans variable does not significantly affect the dividend statistically.Keywords : Cooperation, Credit Union.